Integrated Community Development in Rural Border Region (Case Studi in Tanjung Hulu Village, Nunukan, North Kalimantan) - Suryanto, D (KnE Social Sciences, 2018)
Tanjung Hulu is a village in Lumbis, a district in Nunukan area, North Kalimantan Province. The village is included as one of villages located in the border area of Indonesia, bordering directly Malaysia. Based on geography, demography and social phenomena that are growing and developing in the community, three main problems were found in the area. There are economic problems and poverty, low quality of educational and poor public health quality. The CEGs (Community Engagement Grants) programs that have been applied are the economic development programs to increase the productivity of society based on the primacy of human resources and local natural resources, educational programs to improve school facilities and learning methods, and public health programs to improve the general health of the community. There were five methods used to approach the community and solving the problems, which are assessment, group discussion, problem-solving, advocacy, and recommendations. The results are constructed filial primary school, classroom facilities repair, Taman Baca improvement, PHBS enhancement for children and family, nationality enhancement for students, increasing skills of women community (PKK), and joining hands with Posyandu to provide health services to the community. Keywords: community, economic, educational program, public health